Amphetamine use as a predictor of cardiovascular and cerebrovascular mortality and morbidity: a longitudinal cohort study of criminal justice clients - Ada Åhman; Jonas Berge; Anders Håkansson (Frontiers in Cardiovascular Medicine)
IntroductionAmphetamine use is an increasing problem, and studies suggest a connection between amphetamine use and cardiovascular and cerebrovascular pathology. However, few long-term studies examine amphetamine users' risk of cardiovascular and cerebrovascular pathology, in comparison to users of other drugs. In addition, in a criminal justice system, illicit drug use and psychiatric comorbidity is common, whereas structured treatment and follow-up is uncommon, and stimulant use is common in this setting. The aim of this study was to investigate the risk of cardiovascular and cerebrovascular morbidity and mortality for intravenous drug users with different drugs as the primary drug, using data from the criminal justice system.MethodsA cohort of injecting substance users (N = 2,422) was identified in the Swedish criminal justice system through interviews with the Addiction Severity Index (ASI) between January 2001 and August 2006. Data on age, sex, self-reported injection drug, tobacco use, and time in prison or custody were retrieved from the ASI database. The clients were followed in national registers up to 2014 with respect to cardiovascular and cerebrovascular morbidity and mortality. Potential predictors of cardiovascular and cerebrovascular events were investigated.ResultSelf-reported main drug was amphetamine in 51.5% (n = 1,247), polysubstance use in 33% (n = 799), and heroin in 15.5% (n = 376) of the cohort. Total observational time for the entire cohort was 23,911 person-years [median 10.3 years (IQR 9.3–11.2 years)]. The highest incidence rates of both cardiovascular and cerebrovascular events were found among amphetamine users. Bivariate analyses showed a significantly higher percentage of cardiovascular events in amphetamine users compared to other substance users (p < 0.044). Amphetamine was not significantly associated with cardiovascular or cerebrovascular events, compared to the main drug heroin or polysubstance use.ConclusionIn this study on substance-using criminal justice clients, while the highest incidence rates of both cardiovascular and cerebrovascular events were found among amphetamine-using individuals, the study did not provide evidence of an independent association. The study highlights the need to take co-factors into account, such as comorbidities and socio-economic factors. More studies are needed to distinguish substance-specific pathology from the impact of other unhealthy lifestyle factors among substance-using individuals.